Double-crosslinking self-enhanced hydrogel based on endogenous glucose in-situ initiation as well as preparation method and application of double-crosslinking self-enhanced hydrogel

By using endogenous glucose-induced in situ double cross-linked self-reinforcing hydrogels, and utilizing glucose oxidase and calcium carbonate to form a dual network, the mechanical strength and stability issues of hydrogels in soft tissue filling are solved, achieving high strength, injectability and long-term stability, thus meeting the application requirements of soft tissue filling.

CN121360285APending Publication Date: 2026-01-20SICHUAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511683328.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-17
Publication Date
2026-01-20

AI Technical Summary

Technical Problem

Existing hydrogels have problems such as insufficient mechanical strength, poor injectability and poor long-term stability in soft tissue filling. In particular, single-network hydrogels are prone to swelling and disintegration after implantation, making it difficult to meet the needs of soft tissue filling.

Method used

A double-crosslinked self-reinforcing hydrogel initiated in situ by endogenous glucose is used. Hydrogen peroxide and an acidic environment are generated by glucose oxidase catalysis, forming a covalent network of hyaluronic acid-tyramine. At the same time, calcium carbonate dissolves and releases calcium ions to crosslink with sodium alginate, constructing a dual network to achieve synergistic optimization of mechanical properties and stability.

Benefits of technology

It achieves high mechanical strength and long-term stability of hydrogels in soft tissue filling, and has excellent injectability and rapid gelation ability, meeting the application requirements of soft tissue filling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121360285A_ABST
    Figure CN121360285A_ABST
Patent Text Reader

Abstract

The invention discloses bi-crosslinking self-reinforced hydrogel based on endogenous glucose in-situ initiation as well as a preparation method and application of the bi-crosslinking self-reinforced hydrogel, and relates to the technical field of biomedical materials. The double-crosslinking self-enhanced hydrogel is prepared from the following components in concentration: 1 to 3 weight percent of hyaluronic acid-tyramine, 0.8 to 1.2 weight percent of sodium alginate, 1 to 100 mmol / L of calcium carbonate, 0.0001 to 10 U / mL of horse radish peroxidase, 20 to 40 U / mL of glucose oxidase and the balance of ultrapure water. The invention also discloses an application of the double-crosslinking self-reinforced hydrogel in preparation of a filling and repairing product for soft tissue defects. The hydrogel disclosed by the invention can be filled in a tissue defect part in an injection manner, glucose in body fluid is utilized to initiate crosslinking in situ to form the hydrogel with excellent mechanical properties and long-term stability, and meanwhile, the hydrogel is good in biocompatibility and relatively high in application value.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of biomedical materials, in particular to a double-crosslinking self-reinforced hydrogel based on in-situ glucose-induced and a preparation method and application thereof. BACKGROUND

[0002] With the progress of medical technology, the filling and repair of soft tissue defects has been relatively mature, and the selection of filling materials has become the key to determining the repair effect. Among various filling materials, pre-formed hydrogels have good application value due to their controllable shape and size and mechanical properties, but they cannot completely conform to the implanted site after implantation, and they need to be implanted by surgery, which leads to a complex process, easy wound infection, poor repair effect, and limited application. Compared with pre-formed hydrogels, injectable hydrogels have the advantages of convenient operation, small trauma, and fast recovery, but due to the compromise of injectability, the mechanical strength of the gel is often difficult to meet the application scenarios of most soft tissues. Therefore, in-situ formed hydrogels based on this become another preferred choice for soft tissue filling. Among them, the in-situ gelation methods are diverse, and the common stimulus conditions include light, temperature, pH, ion concentration, and enzymes. However, these methods often need to rely on external application of stimuli or the introduction of chemical initiators, for example, in the photo-crosslinking system, a specific wavelength light source needs to be used for irradiation, which may cause local tissue thermal damage; ion crosslinking needs to introduce high-concentration metal ions, which has potential cytotoxicity; enzyme crosslinking often needs to add additional crosslinking agents, which may cause inflammatory reactions. These factors limit their wide application in clinical practice, especially in soft tissue filling.

[0003] Hyaluronic acid (HA) as a natural acidic mucopolysaccharide is widely used to construct biomedical hydrogels due to its excellent biocompatibility and biodegradability. Although this system has the characteristics of rapid gelation, the single-network hydrogel formed has great deficiencies in mechanical properties and long-term stability, which is difficult to meet the requirements of material strength and durability for soft tissue filling. Although sodium alginate-calcium ion hydrogel also has good biocompatibility, its mechanical properties are usually weak, and the structural stability is poor, and it is easy to swell, disintegrate or change shape due to ion migration or exchange under high load or long-term implantation environment, which is difficult to meet the use scenarios of soft tissue filling materials. SUMMARY

[0004] In order to solve the above technical problems, the purpose of the present application is to provide a double-crosslinking self-reinforced hydrogel based on in-situ glucose-induced and a preparation method and application thereof. The hydrogel of the present application can be filled in the soft tissue defect site by injection, and the in-situ crosslinking is induced by glucose in the body fluid to form a hydrogel with excellent mechanical properties and long-term stability, and the biocompatibility is good, and the application value is high.

[0005] The technical scheme for solving the above technical problems is as follows: a double crosslinking self-reinforced hydrogel based on in-situ initiation of endogenous glucose is provided, which comprises the following components in the following concentrations: hyaluronic acid-tyramine 1-3 wt%, sodium alginate 0.8-1.2 wt%, calcium carbonate 1-100 mmol / L, horseradish peroxidase 0.0001-10 U / mL, and glucose oxidase 20-40 U / mL, and the balance is ultrapure water.

[0006] Further, the following components are included: hyaluronic acid-tyramine 1-3 wt%, sodium alginate 0.8-1.2 wt%, calcium carbonate 50-100 mmol / L, horseradish peroxidase 0.0001-3 U / mL, and glucose oxidase 20-40 U / mL, and the balance is ultrapure water.

[0007] Further, the following components are included: hyaluronic acid-tyramine 1-3 wt%, sodium alginate 0.8-1.2 wt%, calcium carbonate 50-100 mmol / L, horseradish peroxidase 0.0001-3 U / mL, and glucose oxidase 20-40 U / mL, and the balance is ultrapure water.

[0008] The application also provides a preparation method of the double crosslinking self-reinforced hydrogel based on in-situ initiation of endogenous glucose, and the steps are as follows: Hyaluronic acid-tyramine is added to ultrapure water and stirred to dissolve, then sodium alginate is added and stirred until uniform, and the pH is adjusted to neutral; calcium carbonate, horseradish peroxidase, and glucose oxidase are sequentially added and mixed until uniform.

[0009] Further, in step (1), the pH is adjusted to 7.0-7.4.

[0010] The hydrogel is filled into a soft tissue defect site by injection, and the in-situ crosslinking reaction is initiated by endogenous glucose in the tissue fluid of the defect site to form a double crosslinking self-reinforced hydrogel, so as to support and fill the soft tissue defect.

[0011] When the hydrogel is placed in a simulated body fluid containing about 5 mmol / L glucose at 37℃, the storage modulus G' of the hydrogel gradually increases from the initial gelation time to 48 h, and the storage modulus at 48 h is 1.5 times or more of the storage modulus at the initial gelation time.

[0012] The preliminary gelation time of the hydrogel in a simulated body fluid containing about 5 mmol / L glucose at 37℃ is not more than 10 min.

[0013] The application also provides a use method of the double crosslinking self-reinforced hydrogel based on in-situ initiation of endogenous glucose, which comprises injecting the double crosslinking self-reinforced hydrogel based on in-situ initiation of endogenous glucose into an environment containing glucose, and initiating the crosslinking reaction by endogenous glucose in the environment.

[0014] The application also provides application of the above-mentioned double-crosslinked self-reinforced gel based on in-situ triggering of endogenous glucose in preparation of a filling repair product for soft tissue defects.

[0015] The application is based on the formation principle of the double-crosslinked self-reinforced hydrogel based on in-situ triggering of endogenous glucose: The hydrogel can be filled in the soft tissue defect site by injection, and the glucose oxidase catalyzes the endogenous glucose to generate hydrogen peroxide and an acidic environment, and the horseradish peroxidase immediately catalyzes the hyaluronic acid-tyramine to form a first heavy covalent network; at the same time, the acidic by-product slowly dissolves the calcium carbonate to release calcium ions, and the calcium ions are coordinated and crosslinked with sodium alginate to form a second heavy ion network. By adjusting the concentrations of the horseradish peroxidase, the calcium carbonate and / or the glucose oxidase, the gelation speed of the hyaluronic acid-tyramine covalent network and the sodium alginate-calcium ion network can be adjusted from significant peak shifting to basically synchronization or slightly ahead, so that the coordination and matching of the two heavy network gelation processes in a reasonable time window are realized, the second heavy network is gradually built inside the first heavy network and interpenetrates with it, and finally the double-network self-reinforced hydrogel with excellent mechanical properties and stability is obtained.

[0016] The endogenous glucose referred to in the application refers to the glucose existing in the body fluid or simulated body fluid itself, and in the in-vitro experiment, a 5 mmol / L glucose PBS solution is used for simulation.

[0017] The application has the following beneficial effects: 1、The application realizes the synergistic optimization of the hydrogel gelation process and mechanical properties through the design of "endogenous glucose triggering + covalent / ionic double-crosslinking kinetics adjustable". 2+ The Ca 2+ network is formed inside the existing skeleton and is self-reinforced. Unlike the existing systems which only rely on single fast or single slow gelation, the application adjusts the concentrations of HRP, CaCO3 and GOX, so that the gelation speed of the hyaluronic acid-tyramine covalent network and the sodium alginate-calcium ion network is in a controllable window: when the HRP concentration is less than or equal to 3 U / mL, the gelation process of HA-Tyr is adjusted from "instantaneous completion" to SA-Ca 2+The formation speed of the SA ionic crosslinking network, so that the first heavy covalent network is gradually formed in the second heavy ionic crosslinking network, forming an interpenetrating gel network, further improving the mechanical strength of the obtained hydrogel. Rheological test results show that the initial storage modulus of the double network hydrogel prepared in the synergistic gelation window is significantly higher than that of the HA-Tyr single network under the same conditions, and the storage modulus can be increased to more than twice the initial value after being placed in a simulated body fluid at 37℃ and about 5 mM glucose for 48 h, while the HA-Tyr single network hardly shows modulus growth under the same conditions, showing the obvious self-reinforcing advantage brought by the "adjustable gelation kinetics + double network synergy" of the present application.

[0018] 2、The double network hydrogel prepared by the present application exhibits good injectability and excellent long-term stability. The present application realizes the injectability of the material while simultaneously constructing a more stable and tight double crosslinking network through the innovative idea of endogenous glucose-induced gel formation and self-reinforcing, thereby solving the application problem that high-strength hydrogels are difficult to inject, injectable hydrogels have low strength, and are difficult to meet the application requirements of soft tissue filling. Thanks to the structural design, the hydrogel exhibits excellent long-term stability, effectively ensuring the stable existence of the gel after placement. Degradation experiments show that the hydrogel can maintain structural integrity for a long time, meeting the long-term retention requirements of soft tissue filling materials, and solving the technical problem of easy degradation and short maintenance time of existing single network hydrogels. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 is a comparison chart of the storage modulus of hydrogels under different initiation modes; Figure 2 is a comparison chart of the storage modulus of hydrogels under different initiation modes; Figure 3 is a comparison chart of the storage modulus of hydrogels under different initiation modes; Figure 4 is a comparison chart of the storage modulus of hydrogels under different initiation modes. DETAILED DESCRIPTION

[0020] The principles and characteristics of the present application are described below, and the examples are only used to explain the present application and are not used to limit the scope of the present application. If no specific conditions are indicated in the examples, conventional conditions or manufacturer's recommended conditions are used. If no manufacturer of the reagents or instruments is indicated, it is a conventional product that can be purchased on the market.

[0021] Example 1 A double crosslinking self-reinforced hydrogel (HA-TYR / SA) based on in situ initiation of endogenous glucose, consisting of the following concentration components: hyaluronic acid-tyramine 2 wt%, sodium alginate 1 wt%, calcium carbonate 50 mmol / L, horseradish peroxidase 3 U / mL and glucose oxidase 30 U / mL, and the balance is ultrapure water; The preparation method is as follows: hyaluronic acid-tyramine is added to ultrapure water and stirred to dissolve, then sodium alginate is added and stirred uniformly, the pH is adjusted to 7.0, and then calcium carbonate, horseradish peroxidase and glucose oxidase are sequentially added and mixed uniformly.

[0022] Example 2 A double crosslinking self-reinforced hydrogel based on in situ initiation of endogenous glucose, comprising the following concentration components: hyaluronic acid-tyramine 1 wt%, sodium alginate 0.8 wt%, calcium carbonate 50 mmol / L, horseradish peroxidase 3 U / mL and glucose oxidase 20 U / mL, and the balance is ultrapure water; The preparation method is as follows: hyaluronic acid-tyramine is added to ultrapure water and stirred to dissolve, then sodium alginate is added and stirred uniformly, the pH is adjusted to 7.2, and then calcium carbonate, horseradish peroxidase and glucose oxidase are sequentially added and mixed uniformly.

[0023] Example 3 A double crosslinking self-reinforced hydrogel based on in situ initiation of endogenous glucose, comprising the following concentration components: hyaluronic acid-tyramine 3 wt%, sodium alginate 1.2 wt%, calcium carbonate 100 mmol / L, horseradish peroxidase 10 U / mL and glucose oxidase 40 U / mL, and the balance is ultrapure water; The preparation method is as follows: hyaluronic acid-tyramine is added to ultrapure water and stirred to dissolve, then sodium alginate is added and stirred uniformly, the pH is adjusted to 7.4, and then calcium carbonate, horseradish peroxidase and glucose oxidase are sequentially added and mixed uniformly.

[0024] Comparative Example 1 A single network hydrogel (HA-TYR), which is different from Example 1 in that it does not contain sodium alginate.

[0025] Comparative Example 2 A single network hydrogel (SA), which is different from Example 1 in that it does not contain hyaluronic acid-tyramine.

[0026] Comparative Example 3 A double network hydrogel (HA-TYR / SA-H-A), which is different from Example 1 in that it does not contain glucose oxidase.

[0027] Comparative Example 4 A single network hydrogel (HA-TYR-H-A) differs from Comparative Example 1 in that it does not contain glucose oxidase.

[0028] Comparative Example 5 A single network hydrogel (SA-H-A) differs from Comparative Example 2 in that it does not contain glucose oxidase.

[0029] Test Example 1 Optimization of Hydrogel Gelation Conditions To determine the optimal gelation conditions for the double crosslinking self-reinforced hydrogel of the present application, orthogonal test design was used to systematically optimize the concentrations of glucose oxidase (GOX), calcium carbonate (CaCO3) and horseradish peroxidase (HRP), the three key factors. The levels of each factor are shown in Table 1.

[0030] Table 1 Concentration Distribution and Identification of Each Component in Orthogonal Test

[0031] Referring to Example 1, hydrogel solutions of different compositions were prepared according to the ratios listed in Table 1, and then mixed with 5 mmol / L glucose solution to initiate the gelation reaction. The resulting hydrogels were allowed to stand at room temperature for 48 hours to allow them to fully crosslink and complete the self-reinforcement process of the second network.

[0032] Dynamic rheology was used to characterize samples A-F using a rotational rheometer. The test was conducted at a constant temperature of 25°C, with a fixed frequency of 1 Hz and a strain scanning range of 0.01% to 10%. Through dynamic amplitude scanning analysis, the storage modulus (G') of each formulation hydrogel was determined as the key indicator for evaluating the mechanical properties of the gel, and the test results are shown in Table 1.

[0033] As shown in Table 1, the optimal gelation conditions for the double crosslinking self-reinforced hydrogel are 30 U / mL of glucose oxidase, 50 mmol / L of calcium carbonate and 3 U / mL of horseradish peroxidase.

[0034] Test Example 2 Effect of Initiation Method To determine the gelation advantage of GOX+glucose, the gelation of Example 1, Comparative Example 1 and Comparative Example 2 was initiated by 5 mmol / L glucose, and the gelation of Comparative Examples 3-5 was initiated by 1 mmol / L hydrogen peroxide and using glucose acid to adjust the pH to 4.5. After standing for 48 h, the hydrogels were placed in a rotational rheometer and dynamic amplitude scanning analysis was performed at a fixed frequency of 1 Hz and a constant temperature of 25°C, with a strain range of 0.01% to 10%. The storage modulus (G') of HA-TYR / SA, HA-TYR, SA, HA-Tyr / SA-H-A, HA-Tyr-H-A and SA-H-A hydrogels was determined, and the results are shown in Table 2. Figure 1 ​

[0035] Depend on Figure 1 It can be seen that for SA single-network hydrogels, the gelation initiation method has little impact on the hydrogel strength; while for HA-TYR and SA dual-network hydrogels, the hydrogel prepared by glucose oxidase + glucose initiation method has significantly better structural stability than that prepared by direct hydrogen peroxide initiation. It is worth noting that, although Comparative Examples 3-5 also contain HA-Tyr and SA-Ca networks, the hydrogel prepared by this method exhibits significantly better structural stability. 2+ Network, but due to the addition of H2O2, the two cross-linking processes occur almost simultaneously, CaCO3 dissolves - Ca 2+ The lack of gradual acidic environment regulation resulted in a final energy storage modulus that was only slightly higher than that of a single network. As can be seen from Example 1 of this invention, the performance improvement of this invention does not stem from the "dual network" itself, but from the synergistic enhancement effect generated by coordinating the gelation rate of the two networks through GOX / HRP / CaCO3.

[0036] Experimental Example 3: Change of storage modulus over time The gels of Examples 1, 1, and 2 were formed by initiating gelation with 5 mmol / L glucose. Gels aged 0 h, 1 h, 4 h, 16 h, 24 h, and 48 h were placed in a rotational rheometer and subjected to dynamic amplitude scanning analysis within a strain range of 0.01% to 10% at a fixed frequency of 1 Hz and a constant temperature of 25 °C. The storage modulus (G') of each hydrogel was determined. The results are as follows: Figure 2 As shown.

[0037] Depend on Figure 2 It can be seen that the storage modulus of the hydrogel prepared in Example 1 gradually increased from 0.8 kPa to 2.4 kPa between 1 and 48 h. Meanwhile, the single-network hydrogel HA-TYR showed no increasing trend in storage modulus after gelation, while the single-network hydrogel SA exhibited low storage modulus and a small increasing trend after gelation. The results indicate that the double-crosslinked self-reinforcing hydrogel of this invention possesses higher mechanical properties and self-reinforcing characteristics. These results meet and far exceed the requirement that "the storage modulus at 48 h is more than 1.5 times that at the initial gelation stage."

[0038] Experimental Example 4: Injectability and In-situ Rapid Gel Formation Performance The hydrogel was prepared according to Example 1. For ease of observation, a small amount of rhodamine B solution was added to the system as a tracer dye. The hydrogel was drawn into a 1 mL syringe and connected to a 27G fine needle. The needle tip was placed in phosphate-buffered saline (PBS) containing approximately 5 mmol / L glucose at 37°C, and injected at a constant rate. The morphological changes of the precursor solution in the solution during injection were recorded and photographed, as shown below. Figure 3 As shown.

[0039] Depend on Figure 3As can be seen, the hydrogel can be successfully extruded through a fine needle, forming a continuous filamentous structure in simulated body fluid, and rapidly loses its fluidity and solidifies within about 1 minute, without any obvious backflow or diffusion. This indicates that the hydrogel has good injectability and can rapidly gel in situ in a glucose-containing environment.

[0040] Experimental Example 5: In vitro degradation The hydrogels of Examples 1, 1, and 2 were gelled using 5 mmol / L glucose. The hydrogels were washed three times in deionized water, then lyophilized in 24-well plates, and the initial weight (M0) was measured. The lyophilized hydrogels were then incubated in a 3 U / mL hyaluronidase solution for 28 days, with the enzyme solution changed every two days. The hydrogels were removed at different time points for washing, lyophilization, and weighing to obtain the remaining weight (M1). Finally, the degradation rate was calculated using the formula: Degradation rate (%) = (M0 - M1) / M0 × 100%. The results are as follows: Figure 4 As shown.

[0041] Depend on Figure 4 It can be seen that the glucose-initiated double crosslinked self-reinforced hydrogel prepared by the present invention has a significantly smaller mass loss within 28 days than the corresponding single-network hydrogel, and the degradation process is slower, indicating that the hydrogel prepared by the present invention has better stability.

Claims

1. A dual cross-linked self-stiffening hydrogel based on in situ glucose endogenous triggering, characterized in that, It comprises the following concentration components: hyaluronic acid-tyramine 1-3 wt%, sodium alginate 0.8-1.2 wt%, calcium carbonate 1-100 mmol / L, horseradish peroxidase 0.0001-10 U / mL and glucose oxidase 20-40 U / mL, and the balance is ultrapure water.

2. The dual cross-linked self-stiffening hydrogel based on in situ glucose endogenous triggering according to claim 1, wherein, It comprises the following concentration components: hyaluronic acid-tyramine 1-3 wt%, sodium alginate 0.8-1.2 wt%, calcium carbonate 1-100 mmol / L, horseradish peroxidase 0.0001-10 U / mL and glucose oxidase 20-40 U / mL, and the balance is ultrapure water.

3. The dual cross-linked self-stiffening hydrogel based on in situ glucose endogenous triggering according to claim 1, wherein, It comprises the following concentration components: hyaluronic acid-tyramine 1-3 wt%, sodium alginate 0.8-1.2 wt%, calcium carbonate 1-100 mmol / L, horseradish peroxidase 0.0001-10 U / mL and glucose oxidase 20-40 U / mL, and the balance is ultrapure water.

4. The method for the preparation of a dual cross-linked self-stiffening hydrogel based on in situ triggering of endogenous glucose of any one of claims 1 to 3, characterized in that, The steps are as follows: Hyaluronic acid-tyramine is added to ultrapure water and stirred to dissolve, then sodium alginate is added and stirred until uniform, and the pH is adjusted to neutral; calcium carbonate, horseradish peroxidase and glucose oxidase are added in sequence and mixed uniformly.

5. The method for preparing a dual cross-linked self-stiffening hydrogel based on in situ glucose endogenous triggering according to claim 4, characterized in that, The pH is adjusted to 7.0-7.

4.

6. The method of using the dual cross-linked self-stiffening hydrogel based on in situ glucose endogenous triggering according to any one of claims 1 to 3, characterized in that, The double cross-linking self-reinforcing hydrogel based on endogenous glucose in situ initiation is injected into an environment containing glucose, and the cross-linking reaction is initiated in situ by using endogenous glucose in the environment.

7. Use of the double cross-linking self-reinforcing hydrogel based on endogenous glucose in situ initiation according to any one of claims 1-3 in the preparation of a filling repair product for soft tissue defects.

Citation Information

Cited By

  • A self-reinforcing osteogenic adhesive based on an alkaline microenvironment, its preparation method and application

    CN122557793A